A review of salt marsh dynamics - Townend, Ian; Fletcher, Caroline; Knappen, Michiel; Rossington, Kate (Water and environment journal : WEJ, 2011)
Salt marshes have been the subject of extensive research over many years. As well as gaining the interest of biologists, physical processes within the marsh have been measured in some detail since at least the 1920s. There have been various attempts to develop a fuller understanding of the inter‐relationship between physical and biological processes within salt marshes. Advances often go in step changes. Over the last 10–20 years, there has been such a change with the ability to capture and manipulate spatial data in sufficient detail to be able to resolve not only surface topography but also variations in vegetation and a number of relevant physical properties. This review paper seeks to highlight the advances in the understanding of salt marsh dynamics and our ability to investigate the relationships between physical and biological properties. Some consideration is also given to the areas that would benefit from new or further research.